HEALING JOURNALING TRAINING FOR PPA SERVICE OFFICERS IN HANDLING VICTIMS OF VIOLENCE AGAINST WOMEN AND CHILDREN IN BOGOR CITY - Martha, Layung Paramesti; Hafzotillah, Hafzotillah (Yayasan Education and Social Center, 2024)
Healing Journaling training is one of the therapeutic methods to deal with violent crimes by officers/assistants of the Bogor City Empowerment and Protection Regional Technical Service Unit (UPTD PPA Bogor City. This healing journaling technique also adopting from the Rational-Emotive Behavioral Therapy (REBT) counseling technique. Healing journaling is one technique that is written expression brought into counseling sessions and discussed with counselors openly, and it becomes a driver of the counseling process. Journaling also helps keep counselors focused on counseling goals even when not in a counseling session. Sharing and discussing the contents of the journal with officers/assistants of the Bogor City Empowerment and Protection Regional Technical Service Unit (UPTD PPA Bogor City) will increase the achievement of counseling and usually increase client insight and discussion around changes in mindset (cognition), feelings (affective) and behavior (conative) of victims of violence cases